Isochrysis galbana and Diacronema vlkianum biomass incorporation in pasta products as PUFA’s source - Fradique, Mónica (2013)
Factors such as an ageing population, increased health care costs and rapid advances in science and technology are likely driving the increase interest among consumers in attaining wellness through diet, which is in turn, fuelling interest in functional foods and changing the way that people eat. Microalgae have been largely cultured and commercialized as food and feed additives, their potential as source of high-added value compounds and their ability to positively affect human’s health due to their original chemical composition, is well known. Considering pasta is a main staple food, the objective of this study was to prepare fresh spaghetti enriched with different amounts of microalgae and to compare the fatty acid profile of pastas before and after cooking, with standard semolina spaghetti. The results show that fatty acid profile of pastas prepared with Isochrysis galbana and Diacronema vlkianum biomass incorporation, presented a high resistance to the thermal treatment applied during the cooking procedure. The increase of the amount of the algae lead to a significant increase of EPA (Eicosapentaenoic Acid) and DHA (Docosahexaenoic Acid) both in raw and cooked pastas, omega-3 fatty acids that can be obtained through seafood.